Artificial Intelligence Adoption and Productivity in Emerging Markets: Firm Level Evidence - Syahrudin, M; Suryani, Irma (Journal Economic Business Innovation, 2025)
Purpose: This research investigates the impact of artificial intelligence adoption on firm productivity in emerging market manufacturing contexts and it also addresses the organisational factors that moderate these relationships.Method: A cross-sectional survey research design was employed to gather data from manufacturing firms in several emerging markets. In this study, hierarchical regression and moderated regression methods were used to test the mediation role of contextual effects regarding AI adoption and productivity.Findings: We find that an adoption of AI has a strong positive effect on firm productivity, which is however strongly contingent to the organisational circumstances. The connection between AI and productivity is moderated by digital infrastructure, human capital, and firm size. More critically, organizational innovation culture is a second-order moderator that enhances the influence of other contextual variables and facilitate them to produce synergetic effects against productivity.Novelty: The study presents the original idea of organizational culture as a meta-moderator in technology adoption models shedding light on how cultural dynamics augment the effects of other organizational capabilities. It thus emanates a rich theoretical framework that clarifies the intricate dynamics of technological and organizational factors in emerging markets settings.Implications: Research findings imply that EM manufacturers intending to deploy AI need to adopt a comprehensive approach involving the use of AI strategies inclusive of all technological infrastructure, human capital learning as well as cultural change. Instead of conceiving AI as an independent technological artifact, firms need to see it as part of an organizational ecology in which optical factors contribute to the productivity payback disposal from AI.